A LABOVIAN NARRATIVE STYLISTIC ANALYSIS OF KAMILA SHAMSIE’S "HOME FIRE" - Fatima tuz Zahra; Mariam Saleem; Amara Faheem; Ruqia Saba Ashraf (International Journal of Contemporary Issues in Social Sciences, 2023)
This research article conducts a meticulous narrative stylistic analysis of Kamila Shamsie’s acclaimed novel "Home Fire" through the lens of William Labov’s narrative schema. The study aims to unravel the intricate narrative structures inherent in the text, with a particular focus on the underlying political and ideological discourse. By applying Labov’s framework, encompassing elements such as abstract, orientation, complicating action, evaluation, resolution, and coda, the analysis delineates the narrative dynamics that shape the experiences of the Pakistani diaspora in post-9/11 UK. Additionally, the study navigates the integration of Labovian narrative analysis with the diverse structural and functional demands of narration. Employing statistical analysis through SPSS, the frequency of narrative structures is quantitatively examined, revealing consistent patterns across chapters. The findings underscore the cohesive narrative tapestry that binds the text, shedding light on the intricate interplay between personal experience and the socio-political backdrop. Finally, the paper discusses the aesthetic implications of the prevalent political and ideological discourse, emphasizing its role in enriching the text’s socio-political depth while concurrently imposing constraints on its aesthetic dimension. This research contributes to the discourse on diasporic literature, offering a nuanced exploration of "Home Fire" in the post-9/11 context.